Hybrid Systems of Soft Computing Technologies in Designing Team Decision for Supply Chain Management Systems of Organizations - Fedotova, Marina A.; Khromova, Sofia A.; Argunovsky, Dmitry I.; Polushin, Pyotr V. (International Journal of Supply Chain Management, 2020)
Abstractâ€”The main objective is development of hybrid systems for adaptive designing and supply chain management / strategizing of team decision â€œpackagesâ€ for design work based on the use of soft computing technologies and system-creative thinking (SCT). An algorithm is proposed, and the results of case studies on predicting the effectiveness and optimal organization of team thinking, as well as designing team solutions using the technical package of social technologies are presented. They are exemplified by developing a system of products and marketing channels (points of contact) of an employer brand (EB) of an organization for individual stakeholder groups. An algorithm has been developed for using a system of hybrid â€œsoft computingâ€ technologies and system-creative thinking in supply chain process of project teamwork; practical calculations have been carried out using this algorithm. The algorithm and systems of models for using â€œsoft computingâ€ for supply chain developed allow us to obtain a synergistic effect from controlling a system of hybrid technologies at various stages of teamwork. The package includes a â€œbasicâ€ technology comprising â€œtraining teamsâ€, and also the formation of a KPI system that characterize team work (units 1 and 2), â€œproductâ€ technologies comprising analysis of team organization thinking, forecasting team performance, team productivity management, as well as supply chain management of project (units 4, 5, 6), and also â€œclosingâ€ technology being a strategizing (adaptive management) of team work (dynamic control of the algorithm as a whole).